Preoperative Evaluation and Surgical Outcome of Cochlear Implantation in NIENT (Bangladesh Journal of Otorhinolaryngology, 2020)
Background: Sensory neural hearing loss (SNHL) is the most common congenital sensory deficit, with an incidence of one to three per 1000 live births. Acoustic deprivation during the first 3 years of life can hinder speech and language acquisition with significant negative consequences on a child’s educational and psychosocial development. The gold standard intervention for permanent severe to profound hearing loss is cochlear implantation. Cochlear implant (CI); is a semi implantable electronic device that bypass the cochlea.Objectives: An observational study was carried out on 40 cases of pre-lingual deaf to find out the causes of pre-lingual deaf, to evaluate the preoperative procedures to set ideal criteria for pre -lingual cochlear implantation and to evaluate surgical procedure and outcome of cochlear implantations.Methods: Evaluation of the candidates included patient medical history, general health checkup, ENT examination, audiometric evaluation, CT and MRI scans, psychological profile of the candidate. A limited cortical mastoidectomy was performed. The facial recess was opened using the fossa of incudis as an initial landmark. The round window niche was visualized through the facial recess about 2 mm inferior to the stapes. A cochleostomy created by drilling over the basal turn of the cochlea anterior and inferior to the annulus of the round window membrane. The electrode array was then carefully inserted through the fenestra into the scala tympani of the cochlea. Electrophysiological testing (Neural Response Telemetry: NRT) was performed to verify the correct placement of active electrodes.Resulst: Among them 22 (55%) were male and 18 (45%) were female. Male female ratio was 1.2:1. Age distribution at implantation was 3.3±1.054(SD). Average hearing loss was 96.4±5.3(SD) dB and in aided audiogram was 63.7±4.6(SD) dB. Overall complications occurred in 10 (25%) cases. Transient facial nerve paresis in 2 (5%), injury of tympanic membrane in 1(2.5%), seroma 4(10%) and delayed otitis media in 1(2.5%) were observed. Major postoperative complications occurred in 2 cases including facial nerve palsy in 1(2.5%) case and spontaneous device failure in 1(2.5%) case.Conclusion: The result of this survey was find out the risk factor of congenital hearing loss. With a thorough preoperative evaluation, we can select proper candidates for CI which is a reliable and safe procedure with a low percentage of severe complication.Bangladesh J Otorhinolaryngol; October 2020; 26(2): 128-135